Hybrid membrane distillation and wet scrubber for simultaneous recovery of heat and water from flue gas - Yusoff, M.H.M. (MDPI AG, 2020)
Flue gas contains high amount of low-grade heat and water vapor that are attractive for recovery. This study assesses performance of a hybrid of water scrubber and membrane distillation (MD) to recover both heat and water from a simulated flue gas. The former help to condense the water vapor to form a hot liquid flow which later used as the feed for the MD unit. The system simultaneously recovers water and heat through the MD permeate. Results show that the system performance is dictated by the MD performance since most heat and water can be recovered by the scrubber unit. The scrubber achieved nearly complete water and heat recovery because the flue gas flows were supersaturated with steam condensed in the water scrubber unit. The recovered water and heat in the scrubber contains in the hot liquid used as the feed for the MD unit. The MD performance is affected by both the temperature and the flow rate of the flue gas. The MD fluxes increases at higher flue gas temperatures and higher flow rates because of higher enthalpy of the flue gas inputs. The maximum obtained water and heat fluxes of 12 kg m-2 h-1 and 2505 kJm-2 h-1 respectively, obtained at flue gas temperature of 99 Â°C and at flow rate of 5.56 L min-1. The MD flux was also found stable over the testing period at this optimum condition. Further study on assessing a more realistic flue gas composition is required to capture complexity of the process, particularly to address the impacts of particulates and acid gases. Â© 2020 by the authors.